Patient’s Discharge Note App for Sarawak General Hospital - Ameerul Arief Aqmal, Othman (Universiti Malaysia Sarawak (UNIMAS), 2020)
Patient management is a broad term with two description groups. One description refers to a software tool that streamlines procedures within a medical practice or hospital, and the other refers to a whole patient and functional care system. Nowadays many hospitals given each department total freedom in management of patient record, mainly patient diagnosis and summary discharge note. Unfortunately, the current approach frequently leads to a ineffectively planned recording framework, misfortune of data, maintenance records and eventually to wastefulness and squandered assets. Resource and Patient Management System (RPMS) integrate many technology elements of clinical data and analysis with operational tools to help make a hospital or clinic more effective. In Sarawak General Hospital (SGH) also face the same situation as above. Nowadays, SGH already started to use web-based management information system in order to cater the problem, it called Patient Diagnostic Discharge Summary (PDDS). The current system is only functional by accessing by doctor’s PC which lead to accessibility, mobility, inefficient of producing discharge report and summary. An Agile methodology has been used as a software development process to develop this application. The proposed application allow user to view their own discharge note and also allow the doctor to edit patient summary from their mobile phone. The application will be implemented by the whole departments or wards in SGH.